Critizm Rationale of A. Hassan Bangil in Validity on Hadith - MZ, Zainuddin (Journal of Asian Scientific Research, 2014)
During the time, hadiths are always subordinated position, so that when the its-dzahir contrary with Al-Qur’an, then the reasonable (hujjah) of this hadith immediately aborted.Consequently, not a few hadiths which have been graded authentic by the scholars (shahih) should be impeached (can not be used as proof/ hujjah). The real, shahih hadith has not contradicted to the Qur’an, hadith is explanatory of the Qur’an. However, interpreting of hadith is not easy. There are differences among ulama of hadith which is caused by the differences of manhaj (mindset). A. Hasan Bangil or A.Hasan, that his rationale is adopted by most of ulama in Indonesia offers some criterions, when a hadith can be used as hujjah (reasonable for adjustment) or not. However, author does not agree with some hadiths which is determined dhaif by A. Hassan. Therefore, in this paper, author tries to explain: First, his biography especially with his background relating to get knowledge. Second, how manhaj is used in determining the degree of validation of hadith. Third, how his rationale can be criticized so seem positive and negative sides and some example hadiths where a contradiction is happen. This paper aims to contribute academically about how ulama determine the degree of validation of hadith, and can be used as a reference for those researchers who active researching on the validity of hadiths.